Dynamics of media writing adapt and connect - Filak, Vincent F.
"Dynamics of Media Writing Third Edition gives students transferable skills that can be applied across all media platforms-from traditional mass media formats like news, public relations, and advertising to emerging digital media platforms. Whether issuing a press release or tweeting about a new app, today's media writers need to adapt their message for each specific media format in order to successfully connect with their audience. Throughout this text, award-winning teacher and college media adviser Vincent F. Filak introduces fundamental writing skills that apply to all media, while also highlighting which writing tools and techniques are most effective for specific media formats and why. User-friendly and loaded with practical examples and tips from professionals across mass media, this is the perfect guide for any student wanting to launch a professional media writing career. The Third Edition highlights recent developments in writing for websites and blogs, new interviews with working journalists on recent changes in the industry, and updated examples to show success digital media writing strategies"--Provided by publisher.
Includes index.
NMGlova (Recommending faculty) AY2022-2023
Keywords: Mass media -- Authorship -- Handbooks, manuals, etc; Journalism